2022
DOI: 10.1128/spectrum.02604-21
|View full text |Cite
|
Sign up to set email alerts
|

Origin, Phylogeny, and Transmission of the Epidemic Clone ST208 of Carbapenem-Resistant Acinetobacter baumannii on a Global Scale

Abstract: ST208 as one of the most prevalent lineages of CRAB has caused several difficult-to-treat infections and outbreaks around the world. However, few studies have focused on evaluating the genetic background differences of ST208 A. baumannii isolated from very distant geographic regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Overall, this suggests that there are at least three XDR CRAB IC2/ST2 sub-lineages occurring in Brazil simultaneously. Interestingly, the Brazilian genomes did not cluster with other IC2/ST2 genomes from South America, suggesting that these Brazilian CRAB IC2/ST2 strains originate from countries in Europe, North America, and/or Asia where CRAB IC2 is prevalent [1]. Although we did not observe relevant differences in the genetic composition of these three Brazilian clusters, except for the capsule, they could be evolving into specific lineages, as seems to have occurred for other South American ICs [27].…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…Overall, this suggests that there are at least three XDR CRAB IC2/ST2 sub-lineages occurring in Brazil simultaneously. Interestingly, the Brazilian genomes did not cluster with other IC2/ST2 genomes from South America, suggesting that these Brazilian CRAB IC2/ST2 strains originate from countries in Europe, North America, and/or Asia where CRAB IC2 is prevalent [1]. Although we did not observe relevant differences in the genetic composition of these three Brazilian clusters, except for the capsule, they could be evolving into specific lineages, as seems to have occurred for other South American ICs [27].…”
Section: Discussionmentioning
confidence: 51%
“…CRAB IC2 is the most prevalent A. baumannii causing outbreaks worldwide [8], however, interestingly, reports of IC2/ST2 are scarce in South America [7]. In fact, in a recent study (2022) on the origin, phylogeny, and transmission of IC2 on a global scale, IC2 from South America was not analyzed [1]. Furthermore, the study concluded that IC2 (ST208/Oxford scheme) may have originated in North America and subsequently evolved into two clades [1].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations